Lateral genetics: An approach to the cloning of potential human chorio-retinal X-linked genes. - Wong, Paul W. (University of Ottawa (Canada), 1992)
At present the cloning of disease genes relies on the application of forward and reverse genetics which requires prior knowledge of either the protein or the location of the gene locus underlying the disorder. In the present study a third alternative, a lateral approach, which focuses in at the level of expressed sequences (mRNA) is examined. This approach is used in the present study to explore its potential in the isolation of X-linked chorio-retinopathy candidate genes. The strategy developed for this approach uses a probe derived by the PCR amplification of a chorio-retinal cDNA library to screen a hamster/human X hybrid genomic library made in $\lambda$ phage vectors. The immediate achievement of this cross screen is the direct association of tissue expression with chromosome specificity. The initial application and evaluation of this approach is presented in the following thesis.
Keywords: Biology, Molecular.